2016
DOI: 10.1089/scd.2016.0107
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Released from Human Umbilical Cord-Derived Mesenchymal Stromal Cells Prevent Life-Threatening Acute Graft-Versus-Host Disease in a Mouse Model of Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Mesenchymal stromal cells (MSCs) are attractive agents for the prophylaxis of acute graft-versus-host disease (aGVHD) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). However, safety concerns remain about their clinical application. In this study, we explored whether extracellular vesicles released from human umbilical cord-derived MSCs (hUC-MSC-EVs) could prevent aGVHD in a mouse model of allo-HSCT. hUC-MSC-EVs were intravenously administered to recipient mice on days 0 and 7 after allo-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 48 publications
3
95
0
Order By: Relevance
“…On the one hand, SC-EVs have been reported to induce the immune response of T helper type 1 (Th1) conversion to T helper type 2 (Th2). For example, SC-EVs drove the shift from Th1 toward Th2 cells and reestablished Th1/Th2 homeostasis by downregulating pro-inflammatory TNF-α and INF-γ and upregulating anti-inflammatory IL-10 or IL-4 (29,44,51,74,76) ( Table 1). Moreover, SC-EVs could also regulate Th2 immune response toward Th1.…”
Section: Stem Cell-derived Extracellular Vesicle Potentials In T Cellmentioning
confidence: 99%
“…On the one hand, SC-EVs have been reported to induce the immune response of T helper type 1 (Th1) conversion to T helper type 2 (Th2). For example, SC-EVs drove the shift from Th1 toward Th2 cells and reestablished Th1/Th2 homeostasis by downregulating pro-inflammatory TNF-α and INF-γ and upregulating anti-inflammatory IL-10 or IL-4 (29,44,51,74,76) ( Table 1). Moreover, SC-EVs could also regulate Th2 immune response toward Th1.…”
Section: Stem Cell-derived Extracellular Vesicle Potentials In T Cellmentioning
confidence: 99%
“…The EVs isolated from patient serum contains three miRNAs (miR-423, miR-199, miR-93), which may be related to the incidence and severity of GVHD [68]; and the expression of CD146, CD31, and CD140-α on EVs surface, is also closely related to the onset of the disease [69]. Traditional MSCs therapy after replacement with EVs for GVHD also showed ideal results, suggesting that MSCs-derived EVs are potential for cell-free therapy for GVHD [58,70]. Kordelas L et al used MSCs-derived EVs instead of MSCs in the patient with GVHD, and the promising results were obtained.…”
Section: Evs As Therapymentioning
confidence: 99%
“…Wang et al instead showed that UCB-MSC-EVs could prevent aGvHD in a mouse model of allo-HSCT by modulating immune responses [10]. The study demonstrated that UCB-MSC-EVs reduce in vivo manifestations of aGvHD, attenuate the associated histological changes, and prolong mice survival.…”
Section: Therapeutic Power Of Msc-evs In Allo-hsct and Gvhdmentioning
confidence: 99%
“…The study demonstrated that UCB-MSC-EVs reduce in vivo manifestations of aGvHD, attenuate the associated histological changes, and prolong mice survival. In fact, in recipient mice a significant decrease of frequency and the absolute number of CD3 + CD8 + T-cells and an increased ratio of CD3 + CD4 + to CD3 + CD8 + T-cells were found [10]. Finally, as reported by Kordelas et al [121], in vitro and in vivo experiments confirmed the decreased levels of different inflammatory cytokines, including IL-2, TNF-α, and IFN-γ, and an increase of anti-inflammatory cytokines, such as IL-10 (Figure 1) [10].…”
Section: Therapeutic Power Of Msc-evs In Allo-hsct and Gvhdmentioning
confidence: 99%
See 1 more Smart Citation